2006
DOI: 10.1007/s00107-006-0114-z
|View full text |Cite
|
Sign up to set email alerts
|

Zum Einfluss des Holzes sowie des Holzaufschlussverfahrens auf das Benetzungsverhalten von Kiefern- und Fichten-Faserstoffen

Abstract: The main objective of this research work was to study the wettability of thermomechanical pulps (TMP) prepared from heart- and sapwood of Scots pine (Pinus sylvestris [L.]). The TMP were prepared at different pulping temperatures (150 °C, 180 °C). Furthermore, thermomechanical (TMP) and chemo-thermomechanical pulps (CTMP) from Norway spruce (Picea abies [Karst.]) were also investigated. In this case both TMP and CTMP were prepared at 140 °C and 180 °C. Sheets of all pulps were prepared according to a method de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…This is in line with our initial hypothesis that the lignin-rich surfaces of high-temperature TMP would lead to better compatibility with the hydrophobic PP matrix and to composites with higher strength. It was shown by Roffael et al [46] and Schneider et al [47] that the higher the temperature during thermomechanical pulping, the lower the wettability and the higher the hydrophobicity of the fibres.…”
Section: Water Absorption and Swelling Of Wpc Based On Tmp Modified W...mentioning
confidence: 98%
See 2 more Smart Citations
“…This is in line with our initial hypothesis that the lignin-rich surfaces of high-temperature TMP would lead to better compatibility with the hydrophobic PP matrix and to composites with higher strength. It was shown by Roffael et al [46] and Schneider et al [47] that the higher the temperature during thermomechanical pulping, the lower the wettability and the higher the hydrophobicity of the fibres.…”
Section: Water Absorption and Swelling Of Wpc Based On Tmp Modified W...mentioning
confidence: 98%
“…This can be attributed to the hydrophobation effect during high-temperature refining. It has been shown that the higher the temperature during thermomechanical refining, the lower the wettability of the fibres, i.e., the higher the hydrophobicity [46,47]. The more hydrophobic fibres may bond better with polypropylene, which in turn will reduce water uptake of the WPC.…”
Section: Water Absorption and Swelling Of Wpc Based On Tmp Modified W...mentioning
confidence: 99%
See 1 more Smart Citation
“…Daraus wird ersichtlich, dass die Prüfblätter mit TMP eine wesentlich schlechtere Benetzung als Prüfblätter mit CTMP aufweisen. Dies steht inÜbereinstimmung mit den Ergebnissen von Schneider et al (2007), wonach CTMP sich schneller benetzen lassen als TMP. Dies ist vermutlich zum einen auf den vergleichsweise höheren Gehalt an hydrophoben Extraktstoffen der TMP zurückzuführen und zum anderen auf das den CTMP anhaftende Alkali, das Extraktstoffe auflöst und die generelle Benetzbarkeit der Fasern mit wässrigen Lösungen verbessert.…”
Section: Ergebnisse Und Diskussionunclassified